Digital adoptions in motion mapping Filipinos' acceptance of mobile payments using e-wallets through the technology acceptance model - Imperial, Gabrielle Mary Jyren S.; Lee, Brando Ric Mikel C.
This study examines the adoption and use of e-wallet among Filipino users, with a focus on the interplay of personal and social factors affecting their perceptions, attitudes, and behavioral intentions. Anchored on the Technology Acceptance Model (TAM) and Protection Motivation Theory (PMT), the research explores how perceived trust, security, threat, efficacy, acceptance, subjective norms, and attitude influence c-wallet behavioural intention. A quantitative survey of 400 Filipino respondents reveals that GCash dominates the market, with users integrating Mobile Payment Systems (MPS) into their daily routines for transactions such as online shopping and money transfers. Despite high adoption rates, concerns about security and trust remain prominent, highlighting areas for improvement. Correlation and regression analyses indicate strong associations between perceived usefulness, attitudes, and behavioral intentions, with trust and security serving as critical determinants. The study underscores the need for service providers to enhance system reliability, implement robust security measures, and tailor strategies to address specific demographic needs. These findings contribute to the broader understanding of technology adoption in emerging markets, offering actionable insights for improving e-wallet platforms and fostering digital financial inclusion.